Convergent views on disordered protein dynamics from NMR and computational approaches - Salvi, Nicola; Zapletal, Vojtěch; Jaseňáková, Zuzana; Zachrdla, Milan; Padrta, Petr; Narasimhan, Subhash; Marquardsen, Thorsten; Tyburn, Jean-Max; Žídek, Lukáš; Blackledge, Martin; Ferrage, Fabien; Kadeřávek, Pavel (Biophysical journal, 2022)
Intrinsically disordered proteins (IDPs) or intrinsically disordered regions (IDRs) is a class of biologically important proteins exhibiting specific biophysical characteristics. They lack a hydrophobic core, and their conformational behavior is strongly influenced by electrostatic interactions. IDPs and IDRs are highly dynamic, and a characterization of the motions of IDPs and IDRs is essential for their physically correct description. NMR together with molecular dynamics simulations are the methods best suited to such a task because they provide information about dynamics of proteins with atomistic resolution. Here, we present a study of motions of a disordered C-terminal domain of the delta subunit of RNA polymerase from Bacillus subtilis. Positively and negatively charged residues in the studied domain form transient electrostatic contacts critical for the biological function. Our study is focused on investigation of ps-ns dynamics of backbone of the delta subunit based on analysis of amide 15N NMR relaxation data and molecular dynamics simulations. In order to extend an informational content of NMR data to lower frequencies, which are more sensitive to slower motions, we combined standard (high-field) NMR relaxation experiments with high-resolution relaxometry. Altogether, we collected data reporting the relaxation at 12 different magnetic fields, resulting in an unprecedented data set. Our results document that the analysis of such data provides a consistent description of dynamics and confirms the validity of so far used protocols of the analysis of dynamics of IDPs also for a partially folded protein. In addition, the potential to access detailed description of motions at the timescale of tens of ns with the help of relaxometry data is discussed. Interestingly, in our case, it appears to be mostly relevant for a region involved in the formation of temporary contacts within the disordered region, which was previously proven to be biologically important.
Keywords: Intrinsically Disordered Proteins; simulace molekulární dynamiky; Protein Conformation; vnitřně neuspořádané proteiny; Magnetic Resonance Spectroscopy; Amides; Molecular Dynamics Simulation; magnetická rezonanční spektroskopie; DNA-Directed RNA Polymerases; amidy; DNA řízené RNA-polymerasy; konformace proteinů